2017
DOI: 10.1016/j.neulet.2016.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and inheritance of neocortical heterotopia in inbred and genetically-engineered mice

Abstract: Cortical function emerges from the intrinsic properties of neocortical neurons and their synaptic connections within and across lamina. Neurodevelopmental disorders affecting migration and lamination of the neocortex result in cognitive delay/disability and epilepsy. Molecular layer heterotopia (MLH), a dysplasia characterized by over-migration of neurons into layer I, are associated with cognitive deficits and neuronal hyperexcitability in humans and mice. The breadth of different inbred mouse strains that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…We have previously described the prevalence and cytoarchitecture of neocortical and cerebellar heterotopia in C57BL/6J mice (Ramos et al, 2008;Toia et al, 2017). Consistent with our previous work, we found that a large proportion of mice had cerebellar and/or neocortical heterotopia.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously described the prevalence and cytoarchitecture of neocortical and cerebellar heterotopia in C57BL/6J mice (Ramos et al, 2008;Toia et al, 2017). Consistent with our previous work, we found that a large proportion of mice had cerebellar and/or neocortical heterotopia.…”
Section: Resultssupporting
confidence: 92%
“…Brightfield microscopy at varying magnifications (4, 20, and/or 40X) was used to screen sections for cerebellar and neocortical malformations. Digital photomicroscopy was used to document malformations according to methods previously used to identify both cerebellar (Van Dine et al, 2013a,b, 2015Ramos et al, 2015) and neocortical malformations (Ramos et al, 2008;Toia et al, 2017). Statistical analysis and creation of graphs were performed via GraphPad Prism version 9.4.0 with significance levels set at a p-value of <0.05.…”
Section: Methodsmentioning
confidence: 99%